2022
DOI: 10.2460/ajvr.21.08.0131
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic copper accumulates in ferrets with and without hepatobiliary disease

Abstract: OBJECTIVE To determine hepatic copper concentrations and zonal distribution in ferrets with and without hepatobiliary disease, validate rhodanine-based qualitative copper scoring and digital copper quantification in ferret hepatic samples, and ascertain whether clinical features predicted copper accumulation. ANIMALS 34 ferrets, including 7 with necroinflammatory disease, 5 with hepatocellular carcinoma, 13 with non-necroinflammatory disease, and 9 with no hepatobiliary disease. PROCEDURES Rhodanine-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…This technique has been used to assess hepatic copper in dogs, cats and ferrets. 18 , 26 , 28 Studies in humans with WD and rats suggested that LA-ICP-MS can be a useful tool for visualizing copper in tissue specimens. 29 31 LA-ICP-MS is the technique where a laser unit is coupled with ICP-MS.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been used to assess hepatic copper in dogs, cats and ferrets. 18 , 26 , 28 Studies in humans with WD and rats suggested that LA-ICP-MS can be a useful tool for visualizing copper in tissue specimens. 29 31 LA-ICP-MS is the technique where a laser unit is coupled with ICP-MS.…”
Section: Introductionmentioning
confidence: 99%